Dog Days - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid (Series), 2009)
Greg Heffley recounts his daily experiences during summer vacation as he tries to live out his ultimate fantasy of spending the days indoors playing video games with no responsibilities and no rules, despite his mother's attempts to pack the summer with outdoor activities and family fun.